(untitled) (Research, Society and Development, 2021)
The growth of the Brazilian market for biological defensive follows a worldwide trend of reducing the use of pesticides in crops, due to international and societal demands for a more sustainable agriculture. The objective of the present work was to evaluate the efficiency of Bacillus subtilis Bs10 as an inoculant for the soybean crop, through the promotion of plant growth and productive performance in the field. Three field experiments were conduct in the municipalities of Porto Nacional and Formoso do Araguaia, Tocantins, Brazil. The treatments used in the experiments were five doses of the B. subtilis Bs10-based product (0, 100, 200, 300 and 400 mL 50 kg of seeds-1), plus one treatment with a commercial B. subtilis-based product. The inoculation of B. subtilis Bs10 provided increases in biomass, agronomic characteristics, plant population and productivity in soybeans under field conditions. There were positive results starting at a dose of 200 mL, with gains in productivity ranging from 28 to 41% in relation to the absolute control treatment, without inoculation of B. subtilis, and from 11 to 42% in relation to the treatment with commercial product. The bio formulated B. subtilis Bs10 should be recommend as a plant growth promoting inoculant in soybean.